2015
DOI: 10.1097/hjh.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-to-radial SBP amplification

Abstract: Major B-R-SBPAmp occurs in healthy people and is higher with increasing age. Furthermore, B-R-SBPAmp contributes to underestimation of radial tonometry derived central SBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…However, we calibrate our signals utilizing brachial DBP and calculated MAP, thus minimizing possible errors. Moreover, recently Picone et al [ 46 ] found that especially in the younger subjects (<40 years) this remains a valid way of calibrating.…”
Section: Discussionmentioning
confidence: 99%
“…However, we calibrate our signals utilizing brachial DBP and calculated MAP, thus minimizing possible errors. Moreover, recently Picone et al [ 46 ] found that especially in the younger subjects (<40 years) this remains a valid way of calibrating.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, amplification of SBP from brachial to radial arteries may compound the error in underestimation of central SBP and central pulse pressure when radial artery waveforms are calibrated using brachial SBP and DBP. 37–40 The magnitude of calibration-induced error may often exceed 10 mmHg for each of SBP, pulse pressure, and DBP, irrespective of brachial cuff BP methods (e.g. auscultation or oscillometry).…”
Section: Task Force Processmentioning
confidence: 99%
“…As alluded to earlier, there is a strong physiological rationale that central aortic BP may be a better predictor of cardiovascular risk than peripheral BP. However, there are myriad issues which plague the accuracy of devices that estimate central BP [31], including: (1) uncertainty on the best waveform calibration method [32]; (2) reliance on cuff BP for calibration of waveforms [33]; (3) failing to account for brachial-radial BP amplification (only applicable to radial tonometry methods) [34][35][36][37]; and (4) device-specific results due to different algorithms for the estimation of BP [31,32,38]. This final point has led to devices that estimate central BP being described as either 'type I' or 'type II' [31].…”
Section: Accuracy Of Estimated Central Aortic Blood Pressure Devicesmentioning
confidence: 99%